Nutritional, antioxidant and sensory properties of functional beef burgers formulated with chia seeds and goji puree, before and after in vitro digestion. (March 2020) - Antonini, Elena; Torri, Luisa; Piochi, Maria; Cabrino, Giorgia; Meli, Maria Assunta; De Bellis, Roberta
Abstract: The addition of chia seeds and goji puree (2.5 and/or 5%) was evaluated in terms of their effects on the fatty acid profile, lipid peroxidation, total phenols and antioxidant capacity of cooked beef burgers. In comparison to control burgers, polyunsaturated fatty acids doubled or tripled in samples containing chia seeds; polyphenols and antioxidant capacities (ORAC, ABTS, DPPH) increased up to 70% and malondialdehyde values were reduced up to 50% in burgers formulated with both ingredients. Polyphenols, antioxidant capacity and lipid peroxidation were also assessed after in vitro digestion. A marked increase of polyphenol bioaccessibility and antioxidant capacity was observed for all samples, but also malondialdehyde values were increased after digestion, especially in samples containing 5% chia seeds. Finally, hedonistic tests were conducted on young (18–30 years), adult (31–60 years) and elderly (>60 years) subjects and the burgers resulted acceptable by all groups, appointing to their potential application as functional burgers.